P740 Sexual quality of life in inflammatory bowel disease: a multi-centre, national-level study. (25th January 2019) - Roseira, J; Magro, F; Fernandes, S; Simões, C; Portela, F; Ana Isabel, V; Patita, M; Leal, C; Lago, P; Caldeira, P; Gago, T; Currais, P; et al.
Abstract: Background: The impact of inflammatory bowel disease (IBD) in sexuality is one of patient's main concerns. Most studies narrowly focus on sexual organic disfunction rather than patient-perceived sexual quality of life. Our aim was to address sexual quality of life in IBD and population controls. Methods: After an initial pilot study in 2016, the authors conducted a multi-centre, cross-sectional case–control design study, using an anonymous self-administered questionnaire. This multi-modal questionnaire included sociodemographic data and four validated instruments: The Short IBD Questionnaire (SIBDQ), Social Desirability Scale (SDS), Sexual QoL Questionnaire-Male/Female (SQoL-M/F), Nine-item Patient Health Questionnaire (PHQ-9). Results were compared against healthy controls. Results: 869 patients (575 Crohn's disease, 294 ulcerative colitis) and 398 population controls fulfilled the questionnaire. Patients' gender (52.7% women vs. 47.3% men) and clustered age (47.5% < 40 years old vs. 49.8% ≥40 years old) were adjusted. There was no difference for the SDS for IBD and controls (7 vs. 7; p = 0.49), meaning the reliability of responses was homogeneous. IBD patients reported a poorer SQoL (men: 77.3 vs. 83.8, p = 0.007; women: 70.4 vs. 81.6, p < 0.001) and a higher incidence of depression (6 vs.5; p < 0.001) than controls. 189 patients scored for moderate–severe depression indicators. For IBD, SQoL was correlated with health-related QoL (HRQoL) measured by the SIBDQ (men: r = 0.48, women: r = 0.45; p = 0.00), and negatively correlated with depression symptoms (men: r = −0.47, women: r = −0.48; p = 0.00). Similarly, perianal disease was associated with a poorer HRQoL and a higher incidence of depression. However, perianal disease did not impact SQoL for male or female patients. Looking closer into the IBD and controls' SQoL scores, male patients struggled with frustration, depression, anxiety and embarrassment. As for female patients, frustration, depression, anxiety, embarrassment, lack of pleasure and confidence loss were reported. In linear regression analysis for men, SQoL was associated with age, marital status and depression (β −1.87 [IC 95% −2.20 −1.53]; p < 0.001). In women, SQoL was associated with depression (β −1.81 [IC 95% −2.11 −1.51]; p < 0.001) only. Conclusions: IBD patients reported a poorer sexual QoL than healthy controls. Moderate–severe depression was highly reported in IBD and was negatively correlated with SQoL. Similarly to what is reported for disease activity in other studies, perianal disease did not impact SQoL. Patients concerns on sexuality were mostly about emotional issues and self-esteem.